Effect of Fosfomycin on Cyclosporine Nephrotoxicity - Juan Antonio Ortega-Trejo; Rosalba Pérez-Villalva; José M. Arreola-Guerra; Victoria Ramírez; José Sifuentes-Osornio; Norma A Bobadilla (MDPI AG, 2020)
Fosfomycin (Fos) has emerged as a potential treatment against multidrug-resistant organisms, however, there has been little work done on its influence on calcineurin inhibitor nephrotoxicity (CIN). This study was designed to evaluate the effect of Fos in combination with cyclosporine (CsA) on CIN. Two sets of experiments were undertaken. In the first, Wistar rats received different doses of Fos: 0, 62.5, 125, 250, and 500 mg/kg. In the second, rats were divided into four groups: control, CsA 15 mg/kg s.c., CsA + fosfomycin 62.5 mg/kg (CsA + LF), and CsA + Fos 500 mg/kg (CsA + HF). CsA was administrated daily for 14 days, whereas Fos administration started on the ninth day followed by two more doses, delivered 48 h apart. The administration of different Fos doses did not alter renal function. In contrast, CsA induced arteriolopathy, hypoperfusion, a reduction in the glomerular filtration rate, and downregulation of eNOS, angiotensinogen, and AT1R mRNA levels. Lower doses of Fos did not modify CIN. Instead, the CsA + HF group exhibited greater hypoperfusion, arteriolopathy, and oxidative stress, and increased mRNA levels of pro-inflammatory cytokines. This study shows that Fos administered by itself at different doses did not cause renal injury, but when it was given repeatedly at high dosages (500 mg/kg) in combination with CsA, it increased CIN through the promotion of greater oxidative stress and renal inflammation.